Rural Industries and Their Role in the Development of Rural Areas and Afghanistan's National Economy - Fayaz Gul Mazloum Yar (Jurnal Indonesia Sosial Teknologi, 2024)
This study explores the role of rural industries in addressing these issues by examining their potential to improve economic conditions in rural areas and their contribution to the national economy. This study aims to examine the role of rural industries in the development of rural areas and their impact on Afghanistan's national economy. Additionally, it seeks to identify the challenges and opportunities for developing these industries and propose strategies for improving their current state. In this study, I aim to address the following questions: What role do rural industries play in the economic development of rural areas in Afghanistan? What are the major challenges to the development of rural industries in Afghanistan? And how can the potential of rural industries be harnessed to strengthen the national economy? This review study utilizes both analytical and descriptive approaches and relies on credible scientific sources and field data. The information collected includes academic articles, government reports, and statistical data related to rural industries in Afghanistan. Data analysis is conducted descriptively and analytically, focusing on the economic, social, and environmental impacts of rural industries. The findings indicate that the development of rural industries can significantly improve the economy of Afghanistan's rural areas. These industries, by creating employment opportunities, increasing income, and reducing poverty, play a key role in strengthening the national economy.